2020
DOI: 10.1111/1471-0528.16115
|View full text |Cite
|
Sign up to set email alerts
|

Child outcomes after amnioinfusion compared with no intervention in women with second‐trimester rupture of membranes: a long‐term follow‐up study of the PROMEXIL‐III trial

Abstract: Objective To assess the effect of transabdominal amnioinfusion or no intervention on long-term outcomes in children born after second-trimester prelabour rupture of the membranes (PROM between 16 +0/7-24 +0/7 weeks) and oligohydramnios. Population Follow up of infants of women who participated in the randomised controlled trial: PPROMEXIL-III (NTR3492). Methods Surviving infants were invited for neurodevelopmental assessment up to 5 years of corrected age using a Bayley Scales of Infant and Toddler Development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Normal neurodevelopment at age two and/or five was seen in 69.2% of children assessed for follow-up, and almost half reported no respiratory problems. This is comparable to the long-term outcomes of the PPROMEXIL-III trial and to other preterm birth studies [8,21,22]. Due to retrospective data collection we have no additional information about the severity of the respiratory problems.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Normal neurodevelopment at age two and/or five was seen in 69.2% of children assessed for follow-up, and almost half reported no respiratory problems. This is comparable to the long-term outcomes of the PPROMEXIL-III trial and to other preterm birth studies [8,21,22]. Due to retrospective data collection we have no additional information about the severity of the respiratory problems.…”
Section: Discussionsupporting
confidence: 77%
“…For inclusion purposes, all women with previable PROM were prospectively registered. Methods and results of this trial are described elsewhere [7,8]. Our cohort study included all women with previable PROM during this time period in the Amsterdam region, irrespective of trial participation.…”
Section: Data Collectionmentioning
confidence: 99%
“…Pulmonary hypoplasia, chorioamnionitis, and orthopedic deformities are the most common short‐term morbidities after pregnancies complicated by very early PPROM, associated with increased risks of adverse neurodevelopmental outcomes caused by both premature birth and its causes. A recent study with long‐term follow‐up revealed that amnioinfusion was not associated with significant neurodevelopmental delay in children born after mid‐trimester PROM 16 . Oligohydramnios is the most important predictor of perinatal morbidity and mortality in pregnancies complicated by very early PPROM 17 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study with long-term follow-up revealed that amnioinfusion was not associated with significant neurodevelopmental delay in children born after midtrimester PROM. 16 Oligohydramnios is the most important predictor of perinatal morbidity and mortality in pregnancies complicated by very early PPROM. 17 Inverse correlations were evident between the volume of residual amniotic fluid and the prevalence of neonatal morbidities.…”
Section: Discussionmentioning
confidence: 99%
“…As there are many questionnaires reflecting cognition and behaviour in children, and not one outcome is the most important outcome, we included a composite outcome to make a distinction for the most affected children. General health ► In a general health questionnaire, developed by our team and used in several previous follow-up studies, [32][33][34] questions will be asked on health and growth (concerning child's current and previous health, including hospital visits, medication and mental health). Health-related problems (assessed in terms of the need for medical specialist consultation and/or paramedical care, medication used in the past 12 months, hospital admissions and/ or need for surgery) will be clustered in categories to provide insight in the range of health-related problems.…”
Section: Composite Abnormal Cognition And/or Behaviour Developmentmentioning
confidence: 99%